Scaffolded Teachers’ TPACK Lesson Design Model (STLDM) in ELT: A Digital Wisdom during Covid-19 Pandemic - Sri Haryati; Issy Yuliasri; Joko Nurkamto; Sri Wuli Fitriati (International Conference on Science, Education, and Technology, 2022)
The massive spread of the Covid-19 pandemic that results in the school closure demands the movement of learning mode from direct interaction to online learning. To satisfy current demand, the learning design needs to be revised, even renew. As technology massively integrated in EFL classroom, the TPACK framework is viewed to be important to maintain the effective technology-rich classroom which also focusing on the content material and pedagogical aspects. This article presents the STLDM (Scaffolded Teachers’ TPACK Lesson Design Model) in ELT as guideline in developing TPACK-based lesson design. Digital wisdom is accommodated in the design since the integration of technology is concerned. This model includes a two-stage development process in which the first step works on constructing the instructional objective, the second stage works and similar to specifying the design goals in determining the decision for achieving the objectives. It is assumed that the model brings betterment in the TPACK of teachers massively and shifts in the lesson design.